# The fast and furious way {:.no_toc} ## Top Let us assume that you know what you are doing. And also let us assume that you notices how extremely slow the "correct" way of communication between Python and C++ is. Well the following section is for you... Questions to [David Rotermund](mailto:davrot@uni-bremen.de) ## On the Python side ```python # If it is a torch tensor then make a "view" to its numpy core np_input: np.ndarray = input.contiguous().detach().numpy() # We need to make sure that the numpy ndarray is C_CONTIGUOUS. # If not then use numpy.ascontiguousarray() to make it so assert np_input.flags["C_CONTIGUOUS"] is True # Input is a 4d ndarray. And I will make sure that this is really the case assert np_input.ndim == 4 # Now I extract the pointer to the data memory of the ndarray np_input_pointer, _ = np_input.__array_interface__["data"] # Also I need the shape information for the C++ program. np_input_dim_0: int = np_input.shape[0] np_input_dim_1: int = np_input.shape[1] np_input_dim_2: int = np_input.shape[2] np_input_dim_3: int = np_input.shape[3] ``` ## On the C++ side Your C++ method needs to accept these arguments ```cpp int64_t np_input_pointer_addr, int64_t np_input_dim_0, int64_t np_input_dim_1, int64_t np_input_dim_2, int64_t np_input_dim_3, ``` Inside your C++ method you convert the address into a pointer. **BE WARNED:** Make absolutely sure that the dtype of the np.ndarray is correctly reflected in the pointer type dtype=np.float32 --> float dtype=np.float64 --> double dtype=np.uint64 --> uint64 If you fuck this up then this will end in tears! ```cpp float *np_input_pointer = (float *)np_input_pointer_addr; // Input assert((np_input_pointer != nullptr)); assert((np_input_dim_0 > 0)); assert((np_input_dim_1 > 0)); assert((np_input_dim_2 > 0)); assert((np_input_dim_3 > 0)); ``` Don't forget that C Contiguous is just a complicated way of saying Row-major order memory layout [Row- and column-major order](https://en.wikipedia.org/wiki/Row-_and_column-major_order). $$M[a,b,c,d] = M[\eta_a \cdot a + \eta_b \cdot b + \eta_c \cdot c + d]$$ with $$\eta_c = n_d$$ $$\eta_b = \eta_c \cdot n_c$$ $$\eta_a = \eta_b \cdot n_b$$